2014
DOI: 10.1016/j.jcomdis.2013.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Increased vocal intensity due to the Lombard effect in speakers with Parkinson's disease: Simultaneous laryngeal and respiratory strategies

Abstract: Purpose The objective of the present study was to investigate whether speakers with hypophonia, secondary to Parkinson’s disease (PD), would increase their vocal intensity when speaking in a noisy environment (Lombard Effect). The other objective was to examine the underlying laryngeal and respiratory strategies used to increase vocal intensity. Methods Thirty-three participants with PD were included for study. Each participant was fitted with the SpeechVive™ device that played multi-talker babble noise into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 40 publications
0
33
0
1
Order By: Relevance
“…In fact, only few case reports showed that the use of such devices improved intelligibility in PD patients [93,106]. Voice and speech changes included both loudness [93] and intelligibility [93,106], but changes in other acoustic features such as pitch, rate, or even subglottic pressure [108] were also observed, since these modifications may have various origins [108]. Since more mitigated results have also been reported [109], the impact of AAF devices and its potential long-term effects still remain to be established.…”
Section: • • Speech Rehabilitation Devices -A Historical Therapymentioning
confidence: 99%
“…In fact, only few case reports showed that the use of such devices improved intelligibility in PD patients [93,106]. Voice and speech changes included both loudness [93] and intelligibility [93,106], but changes in other acoustic features such as pitch, rate, or even subglottic pressure [108] were also observed, since these modifications may have various origins [108]. Since more mitigated results have also been reported [109], the impact of AAF devices and its potential long-term effects still remain to be established.…”
Section: • • Speech Rehabilitation Devices -A Historical Therapymentioning
confidence: 99%
“…The speaker codes M01, M02, M04, M06, M07, M13, M16, and M18 refer to male speakers with PD, and the speaker codes F02 and F03 refer to female speakers with PD. Pre-treatment respiratory and laryngeal aerodynamic data are presented for these speakers in previously published work (Stathopoulos et al, 2014). …”
Section: 1 Materials and Methodsmentioning
confidence: 99%
“…Use of a reflexive response, like the Lombard effect, eliminates the need for conscious control of vocal intensity. The Lombard effect has been successfully used to elicit increased vocal intensity levels in both neurologically-healthy and neurologically-involved individuals (Adams & Lang, 1992; Adams, Moon, Dykstra, Abrams, Jenkins, & Jog, 2006; Darling & Huber, 2011; Lane & Tranel, 1971; Sadagopan & Huber, 2007; Stathopoulos et al, 2014). To date, however, these Lombard-elicited changes in vocal intensity have only been captured in a single application of noise exposure (Adams & Lang, 1992; Sadagopan & Huber, 2007; Shrivastav, Skowronski, Kopf, & Rakerd, 2014).…”
Section: 1 Introductionmentioning
confidence: 99%
“…In addition, deficits in speech breathing lead directly to many of the hallmark characteristics of speech impairment in individuals with PD, including reduced vocal intensity and short utterances. The evidence that current intervention techniques, focused on improving specific speech deficits (i.e., vocal intensity), improve speech breathing is mixed (Huber, Stathopoulos, Ramig, & Lancaster, 2003;Stathopoulos et al, 2014). In fact, focusing on specific speech deficits without directly addressing speech breathing may lead to maladaptive respiratory behavior (Sadagopan & Huber, 2007).…”
mentioning
confidence: 99%